PEMBELAJARAN MENULIS TEKS CERITA INSPIRATIF BERBANTUAN MEDIA AUDIO VISUAL TIKTOK PADA PESERTA DIDIK KELAS IX DI SMP AL-IHSAN CIMENCRANG - Aruni Husnayaini; Dindin Muhammad Zainal Muhyi; Meity Suratiningsih (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The purpose of this study was to improve the ability of students to write inspirational story texts, to determine the effectiveness of learning to write inspirational story texts using TikTok audio-visual media, and to determine the differences in students' abilities in writing inspirational story texts between experimental classes using TikTok audio-visual media and control classes using conventional media. The method used in this study is a quasi-experiment. Data collection techniques in the form of literature review, trials, test techniques, observation, and analysis techniques. The data obtained were pretest and postest data from experimental and control classes of grade IX students of SMP Al-Ihsan Cimencrang. The results showed (1) there is an increase in the ability of students in learning to write inspirational story texts using TikTok audio-visual media from the average pretest score of the experimental class of 31.54 increased to 86.92 at the time of postes, (2) TikTok audio-visual media is effectively applied in learning to write inspirational story texts compared to image media, this is evidenced by the mann whitney testwith a significance result of 0.000. Because the value of Sig. 0.000 < 0.05, the hypothesis stating that TikTok audio-visual media is effective in learning to write inspirational story texts is accepted, (3) there is a difference in student learning outcomes between the experimental class and the control class in learning to write inspirational story texts, in the experimental class an average postes score of 86.92 was obtained, while in the control class an average of 56.92 postes was obtained.